Achievement goals model validation: Is the 2X2 better than the Trichotomous? - Bilson Simamora; Elisabeth Vita Mutiarawati (International Journal of Evaluation and Research in Education (IJERE), 2021)
Achievement motivation evolved fast in the educational field. In this development, the trichotomous and the 2X2 models received myriad attention from the educational specialist. However, there is a debate about which is better between the two models. This study aimed to intercede this debate and argue that the study's duration should be accounted for in the validation. Approach goals should dominate new students' achievement goals, and old students' achievement goals will show the balance of approach and avoidance goals. For these reasons, this study gathers the data from 350 new students and 203 old students. Confirmatory factor analysis reveals that the trichotomous is the best model for new student segments. While for the old student segment, the 2X2 model shows its efficacy. Therefore, for the new students' segment, achievement goals consist of mastery-approach, performance-approach, and performance-avoidance goals. For the old students, besides those three-goal orientations, mastery-avoidance goals are also included. As expected, the independent sample t-test shows that new students have higher mastery-approach and performance-approach goals than old students have. Self-efficacy is more influential in the new than old student segments, as shown by simple linear regression. This study is still stuck to a single cross-sectional design. Further research can utilize longitudinal research with segmental-based analysis and pay attention to gender, major, social class, or other potential moderation variables.